Towards legacy enablement using web services leverage legacy systems with SOA. - Anand, Dr. Sriram
Legacy systems are a core asset at many organizations. These legacy systems have been around for decades and have a very critical impact on day to day business processes. However, owing to a variety of reasons, these legacy systems have high TCO and represent a bottleneck towards the emergence of an agile IT portfolio. In this article we'll focus on a variety of options that may be available for the seamless integration of legacy systems with an enterprise IT portfolio. We converge on legacy enablement using Web services as a viable option towards achieving an integrated, agile architecture that leverages open standards for communicating with legacy systems. We also evaluate alternative options of legacy integration and identify tools that may be used to simplify integration with legacy systems.